Effects of Amelogenin on Proliferation, Differentiation, and Mineralization of Rat Bone Marrow Mesenchymal Stem Cells In Vitro - Masanobu Izumikawa; Keijiro Hayashi; Mohammad Ali Akbor Polan; Jia Tang; Takashi Saito (The Scientific World Journal)
The aim of this study was to clarify the function of amelogenin, the major protein of enamel matrix derivative, on the proliferation, differentiation, and mineralization of cultured rat bone marrow stem cells (BMSCs), toward the establishment of future bone regenerative therapies. No differences in the morphology of BMSCs or in cell numbers were found between amelogenin addition and additive-free groups. The promotion of ALPase activity and the formation of mineralized nodules were detected at an early stage in amelogenin addition group. In quantitative real-time RT-PCR, mRNA expression of osteopontin, osteonectin, and type I collagen was promoted for 0.5 hours and 24 hours by addition of amelogenin. The mRNA expression of osteocalcin and DMP-1 was also stimulated for 24 hours and 0.5 hours, respectively, in amelogenin addition group. These findings clearly indicate that amelogenin promoted the differentiation and mineralization of rat BMSCs but did not affect cell proliferation or cell morphology.